Elevated markers of gut leakage and inflammasome activation in COVID‐19 patients with cardiac involvement. (8th October 2020) - Hoel, H.; Heggelund, L.; Reikvam, D. H.; Stiksrud, B.; Ueland, T.; Michelsen, A. E.; Otterdal, K.; Muller, K. E.; Lind, A.; Muller, F.; Dudman, S.; Aukrust, P.; et al.
Abstract: Background: A high proportion of COVID‐19 patients have cardiac involvement, even those without known cardiac disease. Downregulation of angiotensin converting enzyme 2 (ACE2), a receptor for SARS‐CoV‐2 and the renin‐angiotensin system, as well as inflammatory mechanisms have been suggested to play a role. ACE2 is abundant in the gut and associated with gut microbiota composition. We hypothesized that gut leakage of microbial products, and subsequent inflammasome activation could contribute to cardiac involvement in COVID‐19 patients. Methods: Plasma levels of a gut leakage marker (LPS‐binding protein, LBP), a marker of enterocyte damage (intestinal fatty acid binding protein, IFABP), a gut homing marker (CCL25, ligand for chemokine receptor CCR9) and markers of inflammasome activation (IL‐1β, IL‐18 and their regulatory proteins) were measured at three time points (day 1, 3–5 and 7–10) in 39 hospitalized COVID‐19 patients and related to cardiac involvement. Results: Compared to controls, COVID‐19 patients had elevated plasma levels of LBP and CCL25 but not IFABP, suggesting impaired gut barrier function and accentuated gut homing of T cells without excessive enterocyte damage. Levels of LBP were twice as high at baseline in patients with elevated cardiac markers compared with those without and remained elevated during hospitalization. Also, markers of inflammasome activation were moderately elevated in patients with cardiac involvement. LBP was associated with higher NT‐pro‐BNP levels, whereas IL‐18, IL‐18BP and IL‐1Ra were associated with higher troponin levels. Conclusion: Patients with cardiac involvement had elevated markers of gut leakage and inflammasome activation, suggestive of a potential gut‐heart axis in COVID‐19. Abstract :